Theory and practice - a case study of coordination and ownership in the Bangladesh health SWAp - Tomson Göran; Forsberg Birger; Sundewall Jesper (BMC, 2006)
Abstract Background In the past decade the sector-wide approach (SWAp) model has been promoted by donors and adopted by governments in several countries. The purpose of this study is to look at how partners involved in the health SWAp in Bangladesh define ownership and coordination, in their daily work and to analyse the possible implications of these definitions. Methodology The study object was a process of decision-making in the Government of Bangladesh in 2003. Information was collected through participant observations, interviews and document review. Results During the study period the Government of Bangladesh decided to reverse a decision to unify the two wings of the Ministry of Health and Family Welfare. The decision led to disagreements with development partners, which had serious implications for cooperation between key actors in the Bangladesh health sector leading to deteriorated relationships and suspension of donor funds. The donor community in itself was also in disagreement which led to inconsistencies in the dialogue between the development partners and the Government of Bangladesh. Conclusion The case shows that main actors in the Bangladesh health SWAp interpret ownership and coordination, fundamental aspects of SWAp, differently. As long as work ran smoothly, the different definitions did not create any problems, but when disagreements arose they became an obstacle. It is concluded that partners in development should devote more effort to their working relationships and that responsibilities within a SWAp need to be more clearly delineated.